Assessment of water availability and irrigation scheduling of right bank canal of Chalakudy river diversion scheme - ANJANA K JITHU MARY VARUGHESE VIVEKANAND VIDYARTHI; Dr. Rema K. P (Guide) (Tavanur 2015 Department of Irrigation & Drainage Engineering)
This study was done to evaluate the performance of canal supply of the RBC of CRDS. In particular, this study deals with the comparison of crop water requirement and irrigation scheduling of the proposed and present cropping pattern in the command area of the RBC, the computation of scheme supply for the proposed and present cropping pattern and thereby to estimate the adequacy of the canal supply system.
Assessment of water availability and irrigation scheduling of right bank canal of Chalakudy river diversion scheme